Exploring a novel nickel source for tropical agroecosystems - Rodak, Bruna Wurr (2018)
The management of acidic soils with by-products promotes the reuse of these materials allowing combined agricultural practices (e.g., liming and fertilization), which increases the sustainability of food production chains. Mining by-products, such as petroleum coke ashes, can be efficient soil acidity amendments while providing Ni – an important micronutrient – to plants. Emergent in agriculture, Ni is a constituent of urease and hydrogenase, two key enzymes in N metabolism. Crop fertilization with this micronutrient, although promising, still needs to be better understood. This study investigated the beneficial use of petroleum coke ashes in agriculture as a Ni-rich soil acidity amendment, as well as the effects of Ni fertilization on the soil-plant system. In the first part of the study, the physical, chemical, and mineralogical properties of the ashes were assessed to create a product called blended limestone (BL). Its agronomic and environmental feasibility was tested under greenhouse conditions, with different soils and cultivated plants. The BL corrected soil acidity and provided nutrients to the plants, also functioning as a Ni fertilizer. In this way, this product is a viable and sustainable technology for promoting the beneficial use of byproducts of petroleum coke in agriculture. In the second part of the study, we investigated short-term residual effects of Ni application on the soil-plant system, as well as environmental and food safety aspects of such application. For this purpose, a single application of Ni-rich soil amendments (one containing a Ni-rich by-product – BL – and one containing a Ni salt) was evaluated under field conditions, after two cropping seasons. The enriched sources provided Ni to the plants and neutralized soil acidity. In the first cropping season, Ni reached optimal levels in soils and plants, promoting yield and physiological gains in plants. Small residual effects of Ni levels were observed in the second year, yet yield gains were no longer observed. No negative impacts to the environment and to food safety were verified following the application of Ni. Our data suggest that fertilization with this micronutrient may require year-to-year adjustments via Ni-fertilizers and should be monitored. The combined results of both parts of our study allow us to conclude that in addition to generating new knowledge concerning Ni fertilization in agriculture, we have also developed a viable and sustainable technology for reusing by-products from the mining industry in agroecosystems, making it possible the combination of soil management practices that contribute to greater efficiency of the cropping system. A better management and an efficient use of resources through integration of productive chains in the mining industry and in agriculture are actions in line with goal 12 – Ensure sustainable consumption and production patterns – of the 2030 Agenda for Sustainable Development.